KONSEP DAN IMPLEMENTASI KURIKULUM MERDEKA BELAJAR PADA LEMBAGA PENDIDIKAN DASAR : (STUDI KASUS DI SDN KARPOTE 2 BLEGA BANGKALAN) - Rohman, Syaiful; Tohari, Mustofa; Ishaq Syahid (Jurnal Edukasi Pendidikan Guru Madrasah Ibtidaiyah, 2026)
Abstract The goal of the independent learning curriculum is to provide students with a wide range of relevant competencies and skills to be developed in the future. This is coupled with a radical (deep and deeply rooted) understanding and practice of monotheistic values, freedom to choose their chosen field of study, and learning practices that reflect future needs and projections. This article uses a qualitative case study approach, where researchers conduct in-depth explorations of programs, events, processes, and activities involving one or more individuals. A case study is bound by time and activity, and researchers collect detailed data using various data collection procedures over a continuous period. Teachers' perspectives on the independent learning curriculum concept significantly impact their readiness to implement it in elementary schools or madrasas. Age, reluctance to develop personal capacity or learn IT, and reluctance to apply various methods using innovative learning media are key obstacles. On the other hand, limited infrastructure, such as mobile devices or laptops, also poses a barrier to the implementation of digital-based learning, making it difficult to innovate with current learning models. Keywords: Elementary education institutions, Concept and Implementation of the independent curriculum